Procedural justice under the principle of legality in South African administrative law - Steytler, Isabeau Elizabeth (Department of Public Law, 2026)
The South African Constitution provides everyone with a right to administrative action that is procedurally fair. This right is given legislative effect in the Promotion of Administrative Justice Act (PAJA), under which the requirements of procedural fairness are broadly applicable and robust. The application of procedural fairness under the Constitution and the PAJA is however limited to those exercises of public power classified as ‘administrative action'. In giving meaning to the concept of administrative action under the Constitution, the Constitutional Court has excluded from its ambit, executive, legislative and judicial action, while the PAJA excludes a multiplicity of additional exercises of public power. There are accordingly a large number of exercises of public power that are not reviewable as administrative action (non-administrative action). Non-administrative action is, however, not exempt from judicial oversight. It is subject to the principle of legality, which was developed by the Constitutional Court as a safety net to ensure that all exercises of public power are subject to some standards of review. It has thus far been developed to include review for lawfulness and rationality and it was expected that when the appropriate case arose, it would be developed to include review for procedural fairness. When that case arose, however, the Constitutional Court found that procedural fairness was not a requirement under the principle of legality. The result was an all-or-nothing divide in respect of procedural fairness: while administrative action is subject to the potentially extensive requirements of procedural fairness under the PAJA, non-administrative action is not subject to procedural fairness at all. When subsequently faced with facts that cried out for the application of procedural fairness, the Constitutional Court did not reverse or limit its finding but found that consultation (usually the remit of procedural fairness) could in certain circumstances be required as a matter of rationality, a ground that became known as ‘procedural rationality'. The courts have subsequently relied on procedural rationality as a basis for requiring consultation in certain circumstances. When doing so, they have noted that procedural rationality is not to be conflated with procedural fairness, as it is rooted within the concept of rationality, and that requiring consultation under procedural rationality is therefore not at odds with the inapplicability of procedural fairness under the principle of legality. The difference between procedural fairness and procedural rationality is significant. Rationality is concerned only with the logical connection between the means and ends of a decision, while fairness is concerned far more expansively with the dignity and fair treatment of affected persons, the value of providing decision-makers with all the facts, and the public importance of justice not only being done but also being seen to be done. The research question of this thesis is therefore, given the conceptual differences between procedural fairness and procedural rationality, can procedural rationality effectively fill the gap left by the exclusion of procedural fairness from legality review where consultation is necessary in order to achieve procedurally just outcomes? The conclusion arrived at is that procedural rationality is not capable of fulfilling the role of procedural fairness under the principle of legality for a number of reasons stemming from its conceptual underpinning in rationality rather than fairness. The thesis recommends three alternative ways in which this gap could nevertheless be addressed.